Amiloride-Sensitive Sodium Channels and Pulmonary Edema - Althaus, Mike; Clauss, Wolfgang G.; Fronius, Martin (Pulmonary Medicine, 2011)
The development of pulmonary edema can be considered as a combination of alveolar flooding via increased fluid filtration, impaired alveolar-capillary barrier integrity, and disturbed resolution due to decreased alveolar fluid clearance. An important mechanism regulating alveolar fluid clearance is sodium transport across the alveolar epithelium. Transepithelial sodium transport is largely dependent on the activity of sodium channels in alveolar epithelial cells. This paper describes how sodium channels contribute to alveolar fluid clearance under physiological conditions and how deregulation of sodium channel activity might contribute to the pathogenesis of lung diseases associated with pulmonary edema. Furthermore, sodium channels as putative molecular targets for the treatment of pulmonary edema are discussed.